2013
DOI: 10.1183/09031936.00097412
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sensitisation to pollens and moulds on seasonal variations in asthma attacks

Abstract: No large study has described the seasonal variation in asthma attacks in population-based asthmatics in whom sensitisation to allergen has been measured.2637 young adults with asthma living in 15 countries reported the months in which they usually had attacks of asthma and had skin-prick tests performed. Differences in seasonal patterns by sensitisation status were assessed using generalised estimating equations.Most young adults with asthma reported periods of the year when their asthma attacks were more comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 40 publications
2
42
0
5
Order By: Relevance
“…in a large epidemiological study [26], and grass pollen counts were found to be responsible for asthma attacks at the primary care level [27]. The reasons for increases in susceptibility to developing allergy in response to exposure to pollen allergens remain elusive, but environmental and lifestyle factors appear to drive increases.…”
Section: Pollen and Mould Allergymentioning
confidence: 99%
“…in a large epidemiological study [26], and grass pollen counts were found to be responsible for asthma attacks at the primary care level [27]. The reasons for increases in susceptibility to developing allergy in response to exposure to pollen allergens remain elusive, but environmental and lifestyle factors appear to drive increases.…”
Section: Pollen and Mould Allergymentioning
confidence: 99%
“…Полученные нами резуль-таты распространенности сенсибилизации пациентов к аллергенам злаковых трав, а также частота выявления диагностически значимого уровня IgE-антител к иссле-дуемым аллергенам согласуются с данными A. Navarro, который показал, что к пыльце растений сенсибилизиро-вано не менее 51% пациентов с аллергическим ринитом и не менее 43% с бронхиальной астмой [14]. В работе C. Canova, описывающей масштабное исследование по рас-пространенности сенсибилизации к злаковым травам, также показано, что в Северной Европе от 28 до 49% па-циентов с бронхиальной астмой в зависимости от региона исследования имеют положительные результаты кожного тестирования и уровень аллергенспецифических IgE, пре-вышающий пороговую границу 0,35 кЕ/л [8].…”
Section: Discussionunclassified
“…Сравнительно недавно Европейским респираторным сообществом охраны здоровья (European Community Respiratory Health Survey, ECRHS) в крупном эпиде-миологическом исследовании была подтверждена пер-востепенная роль пыльцы злаковых трав в развитии ингаляционной аллергии [8]. Особое внимание требует рассмотрение вопроса перекрестной реактивности IgE-антител, развивающейся на гомологичные (имеющие сходную структуру молекул) аллергены.…”
Section: обоснованиеunclassified
See 2 more Smart Citations